2023
DOI: 10.1021/acssuschemeng.2c06864
|View full text |Cite
|
Sign up to set email alerts
|

Facile and General Electrochemical Diselenylation of Terminal Alkynes

Abstract: Difunctionalization of terminal alkynes is a cuttingedge method for producing trisubstituted alkenes. The methods employed, however, rely heavily on the use of organometallic species with harsh conditions or transition metal-catalyzed multicomponent radical-mediated transformations. Herein, we report an electrochemical diselenylation of terminal alkynes to afford trisubstituted alkenes in an antiselective fashion with 100% atom economy. Moreover, this method uses simple graphite as electrodes and MeCN as a sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…. 22 This is a known compound, and the spectroscopic data are consistent with those previously reported. The crude residue was purified by flash column chromatography (SiO 2 ; 8:1 PE/EA), 31 mg, 70% yield, yellow solid, mp 94.0−96.6 °C; 1 H NMR (600 MHz, CDCl 3 ): δ 7.88 (d, J = 8.9 Hz, 2H), 6.95 (d, J = 8.9 Hz, 2H), 4.69 (s, 2H), 4.13−4.10 (m, 2H), 1.45 (t, J = 6.9 Hz, 3H).…”
Section: -(4-ethoxyphenyl)-2-thiocyanatoethan-1-one (3k)supporting
confidence: 88%
“…. 22 This is a known compound, and the spectroscopic data are consistent with those previously reported. The crude residue was purified by flash column chromatography (SiO 2 ; 8:1 PE/EA), 31 mg, 70% yield, yellow solid, mp 94.0−96.6 °C; 1 H NMR (600 MHz, CDCl 3 ): δ 7.88 (d, J = 8.9 Hz, 2H), 6.95 (d, J = 8.9 Hz, 2H), 4.69 (s, 2H), 4.13−4.10 (m, 2H), 1.45 (t, J = 6.9 Hz, 3H).…”
Section: -(4-ethoxyphenyl)-2-thiocyanatoethan-1-one (3k)supporting
confidence: 88%
“…Very recently, Wang and coworkers developed an electrochemical protocol for the diselenylation of terminal alkynes 45a with diselenides 45b under metal- and catalyst-free conditions in an atom- and step-economical manner (Scheme 45). 64 The reactions were carried out in an undivided cell using simple graphite as electrodes and n Bu 4 NBF 4 as an electrolyte at room temperature. An ample range of (hetero)aryl terminal alkynes and even internal alkynes were competent substrates for this transformation.…”
Section: Diselenationmentioning
confidence: 99%
“…50 Recently, Wang et al reported an electrochemically driven diselenylation of terminal alkynes to prepare 1,2-bis-selenyl alkenes (Scheme 14). 51 This method exhibits high tolerance toward various functional groups and is suitable for the late-stage functionalization of alkyne-functionalized drugs. Based on radical trapping experiments and HRMS data analysis, a plausible mechanistic scenario was proposed.…”
Section: Intermolecular Selenofunctionalizationmentioning
confidence: 99%